Investigation of Building Crack on Government Health Clinics in Johor and Negeri Sembilan - BADRIL HISHAM, NURFATIN; MOHAMAD APZAN, NURULAIN SYAMIMI; MOHD FAZLI AZUAR, NURUL AISHAH; MOHAMMAD, HAIRUDDIN (Multidisciplinary Applied Research and Innovation, 2022)
A building may be damaged as a result of cracks. This is a worldwide occurrence that occurs on a regular basis, in a form of structural or non-structural crack. Nevertheless, with regard to the government buildings, this issue needs to be systematically apprehended since it involves the public safety. Therefore, a case study focusing on the government’s health clinics in Johor and Negeri Sembilan is conducted. The objectives are to identify common types of crack on building and its suggestion for rectifications, and to analyses the frequency of cracks in selected buildings. The study uses unpublished UTHM’s consultancy reports, as primary source of data. Further, to achieve the stated objectives, qualitative methods were employed throughout. The processes were assisted by a Multi-Layered Thematic Analysis (MLTA), and Atlas.ti software. The results shows that the common types of cracks occur in buildings, its improvements and the frequency of defects that occur in each government health clinic building in Johor and Negeri Sembilan. The significance of this study for all communities and parties is that once the type of cracks in a building are identified, this information will be used as material and reference for the community in the future. Furthermore, it can be used as a reference for analysts who want to analyses the frequency of building defects. In conclusion, each building crack has its own improvement, and the frequency of defects that develop for each government health clinic is likewise considerable. As a result, future research should focus on improving the usage of software Atlas.ti and crack measurement for each type of crack.